Predictors of smoking cessation among staff in public universities in Klang Valley, Malaysia - Yasin, S.M.; Masilamani, R.; Ming, M.F.; Koh, D. (2011)
Smoking cessation studies are often performed in clinic based settings. The present example aimed to find predictors of success among staff in worksite smoking cessation programmes in two major public universities in Klang Valley, Malaysia. All staff from both universities received an open invitation via staff e-mail and letters to participate. At the start of treatment, participants were administered the Rhode Island Stress and Coping Questionnaire and Family Support Redding's Questionnaire. Behaviour therapy with free nicotine replacement therapy (NRT) were given as treatment. After two months, they were contacted to determine their smoking status. 185 staff from University A (n=138) and University B (n=47), responded and voluntarily showed interest to quit. There was no significant difference in respondents with respect to socio demographic characteristics and smoking history. After two months of treatment, quit rates were 24 in University A vs. 38 in University B (p>0.05). Univariate predictors of cessation were adherence to NRT (p<0.001), smoking fewer cigarettes per day (p<0.05) and the number of behaviour therapy sessions attended (p<0.001). Logistic regression identified 3 significant predictors of smoking cessation. Participants attending more than one session (OR=27.00; 95 CI : 6.50; 111.6), and having higher pre-treatment general stress (OR=2.15; 95 CI: 1.14; 4.05) were more likely to quit, while a higher number of cigarettes smoked (OR=0.19: 95 CI: 0.06; 0.59) reduced the likelihood of quitting. Increasing age, ability to cope with stress and family support were not significant predictors. We conclude that factors such as the number of counseling sessions, the amount of cigarettes smoked at baseline, adherence to NRT and pretreatment stress are important considerations for success in a worksite smoking cessation programme.